2017
DOI: 10.1007/s12282-017-0776-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of miR-130a in cancer

Abstract: MicroRNAs (miRs) are short and highly conserved non-coding RNAs molecules consisting of 18-25 nucleotides that regulate gene expression at post-transcriptional level by direct binding to complementary binding sites within the 3'untranslated region (3'UTR) of target mRNAs. New evidences have demonstrated that miRNAs play an important role in diverse physiological processes, including regulating cell growth, apoptosis, metastasis, drug resistance, and invasion. In chromosomes 11 and 22 of the miR-130 family, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 63 publications
3
65
0
Order By: Relevance
“…Specifically, of the 13 miRNAs included in our signature, there is limited evidence regarding the role of hsa-miR-125-5p in breast cancer progression, while there is some evidence to suggest that miR-301-5p stimulates proliferation and invasion (26) and that hsa-miR-196-5p and hsa-miR-340-5p inhibit progression (27,28). For hsa-miR-30-5p, hsa-miR-130-5p, hsa-miR-93-5p, hsa-miR-503-5p, and hsa-miR-205-5p, there is conflicting evidence regarding their roles in breast cancer progression, with some reports suggesting functions that operate to increase the risk of progression and others suggesting the reverse (29)(30)(31)(32)(33)(34)(35). The apparently conflicting evidence regarding the roles of specific miRNAs in breast cancer prognosis is consistent with the observation that some miRNAs exert both oncogenic and tumor suppressive effects (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, of the 13 miRNAs included in our signature, there is limited evidence regarding the role of hsa-miR-125-5p in breast cancer progression, while there is some evidence to suggest that miR-301-5p stimulates proliferation and invasion (26) and that hsa-miR-196-5p and hsa-miR-340-5p inhibit progression (27,28). For hsa-miR-30-5p, hsa-miR-130-5p, hsa-miR-93-5p, hsa-miR-503-5p, and hsa-miR-205-5p, there is conflicting evidence regarding their roles in breast cancer progression, with some reports suggesting functions that operate to increase the risk of progression and others suggesting the reverse (29)(30)(31)(32)(33)(34)(35). The apparently conflicting evidence regarding the roles of specific miRNAs in breast cancer prognosis is consistent with the observation that some miRNAs exert both oncogenic and tumor suppressive effects (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…miR-130a has recently been demonstrated to be involved in various common human cancer types, including hepatocellular carcinoma, ovarian cancer, glioblastoma, prostate carcinoma, leukemia and cervical cancer (15). Feng et al (16) reported that miR-130a was regulated by nuclear factor (NF)-κB and promoted cervical cancer cell growth by inhibiting the expression of phosphatase and tensin homolog (PTEN).…”
Section: Introductionmentioning
confidence: 99%
“…Both micro-RNAs are involved in cancer. In particular, upregulation of miR-135b promotes chemoresistance (23) and cancer progression (24) in colorectal cancer, whereas miR-130a is associated with drug resistance and acts as an intermediate in the Wnt/b-catenin pathway (25). More importantly, both microRNAs were shown to downregulate KLF4 expression (26), supporting the idea that their decreased expression plays an important role in the 5-ASA-mediated increase in KLF4 expression.…”
Section: Discussionmentioning
confidence: 84%